The impact of China's universal two-child policy on total, preterm, and multiple births: a nationwide interrupted time-series analysis - Yuehang Geng; Lin Zhuo; Rui Zhang; Houyu Zhao; Xinlin Hou; Hu Chen; Lili Liu (BMC Public Health, 2024)
Abstract Background Although years have passed since the implementation of China’s universal two-child policy, the effectiveness of this policy remains unclear. To address this knowledge gap, we, here, assessed the impact of the two-child policy on total live births, preterm births, and multiple live births. Methods Data identifying pregnancies resulting in at least one live birth between April 1 2013 and December 31 2018 were collected from the Hospital Quality Monitoring System database. Using an interrupted time-series analysis, we estimated immediate level changes and long-term trends in total, preterm (birth before 37 weeks’ gestation), and multiple live births that had occurred after July 2016, when the universal two-child policy had taken effect. Results A total of 8,273,622 live births were reported during the study time frame. The number of live births (p = 0.277), preterm births (p = 0.052), and multiple births (p = 0.856) per month slightly increased immediately after July 2016, but these increases did not meet statistical significance. Further, all three outcomes showed a significant downward trend that lasted until the end of 2018 (p < 0.0001 for all). Among all live births, the percentage of preterm births remained stable (p = 0.101), while the percentage of multiple live births that were preterm significantly increased (trend change = 0.21% per month, 95% CI 0.14 to 0.28, p < 0.0001). The percentage of live multiple births among all live births significantly decreased (p for trend = 0.0039). Conclusions Overall, our data reveal a transient baby boom, as well as an increase in the proportion of live multiple births that were preterm, after China’s two-child policy took effect. The latter should be noted by healthcare professionals due to the high risk of complications and special medical care required by preterm babies.